Old actors, new proposals: the IAS as a protagonist in the promotion of socio-emotional skills in the Brazilian Basic Education (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2023)
Actors who traditionally develop articulations in political networks involved in redefining the content of the Brazilian public education have as a characteristic the capillarity so that their proposals welcome unique ideas and reach adherence. In this study, the performance of the Instituto Ayrton Senna (IAS) in promoting socio-emotional skills in the Basic Education curricula is analyzed through the examination of materials (such as guiding documents and journalistic articles), available on its website, which elucidate its action strategies and its formative intentions. With this, it is also sought to clarify its capabilities, the scope of its relationships and the way it prioritizes such content in its proposals, which is done with the theoretical-methodological support of the ethnography of networks.The research problem is summarized in: How does the IAS work to promote socio-emotional skills in the Basic Education curricula? Through the analysis, the constant presence of the IAS in programs and projects that aim to legitimize unique contents in Basic Education is identified, realizing its recent engagement so that socio-emotional skills are appropriated by schools in their practices, acting on different fronts and associating to other different actors. The study points out the engagement of its proposals with the current needs of the productive organization, which has demanded, in the midst of an affective capitalism, the promotion of the subjects’ emotional management.Keywords: Education policies. School curriculum. Socioemotional skills. Political networks. Network ethnography.